Research progress on application of real-time shear wave elastography in kidney disease - QIN Qin; WANG Dan-dan; DANG Wen-zhu; TONG Ming-hui (Linchuang shenzangbing zazhi)
As a novel ultrasound technology for evaluating tissue elasticity,shear-wave elastography has the advantages of non-invasion,quantification and repeatability.It can be used to evaluate the changes in the Young’s modulus of the renal parenchyma in various kidney diseases,providing important information for real-time dynamic monitoring and follow-up.This article intends to review the principles of shear wave elastography and its application in kidney diseases.